Analisis Perbandingan Auotomation Testing Katalon Studio Dan Selenium Ide Pada Website E-Commerce Menggunakan Metode End-To-End (Studi Kasus Enterkomputer.Com) - Andhika Linggar Bhanuwa, Muhammad; Jannah, Miftahul (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2025)
Enterkomputer.com is an E-Commerce website that offers technology and computer products to customers in Indonesia. In facing the rapid growth of online business and tight competition, Enterkomputer.com developers need to ensure that the website operates well, is free from bugs, and provides an optimal shopping experience for users. This can be achieved by conducting regular web testing. This study aims to compare the performance of software testing automation tools, namely Katalon Studio and Selenium IDE, on the E-Commerce websiteEnterkomputer.com using the End-to-End testing method. The study was conducted to analyze the time efficiency, reliability, and effectiveness of both tools in detecting bugs and ensuring service quality. Testing was carried out by repeating five times for each test case on the main features such as login, product search, product details, favorites list, product ordering, and logout. The test results show that Katalon Studio excels in terms of intuitive user interface and feature integration, while Selenium IDE is more flexible in supporting various programming languages. This study provides relevant recommendations for developers to choose the appropriate tool based on specific E-Commerce.